PENGARUH PROGRAM UPAYA KHUSUS (UPSUS) TERHADAP PRODUKTIVITAS, BIAYA POKOK PRODUKSI, DAN PENDAPATAN USAHATANI JAGUNG DI KABUPATEN LAMPUNG TIMUR - Ana Hirdapina; Agus Hudoyo; Achdiansyah Soelaiman (Jurnal Ilmu Ilmu Agribisnis: Journal of Agribusiness Science, 2020)
Corn is one of the food crops that substitutes rice in Indonesia. In 2011-2014 its production had been smaller than its needs and losses. To increase its production, the government had implemented Upaya Khusus (Upsus) program since 2015. The Upsus implementation is successful if yield increases, productionstandard cost decreases, and profit increases. The objective of this study is to analyze the impacts of the Upsus on those three variables. The sampel respondents were chosen by the simple random sampling method. The total respondents were 26 corn farmers from three districts and two villages in each district.  Respondents were interviewed for their farm budget in the four seasons, i.e. rainy season 2014/2015, dry season 2015, rainy season 2017/2018, and dry season 2018. Therefore, the total observation was 104.The dependent variables were yield, production standard cost, and profit. The independent variables were Upsus, Location, and Season. Data were analyzed by the multiple linear regression model. The results of this study was that Upsus has statistically significant impact on increasing its yield (α= 1%), decreasing its production standard cost (α= 5%), and increasing its profit (α =1%). The corn yield increased from 4,88 ton/ha to 5,54 ton/ha, i.e. increase 13%. The corn production standard cost decreased from IDR2,054/kg to IDR1,747/kg, i.e. decrease 15%. The corn profit increased from IDR6.21 million/ha to IDR8.26 million/ha,i.e. increase 33%.Key words: corn, non-Upsus, production standard cost, profit, Upsus, yield